Impact of climate change on potato cultivation: A global perspective - Dua, V K; Chaukhande, Paresh; Sharma, Jagdev; Mankar, Pooja (Indian Horticulture, 2020)
Potato is the third most important food crop in terms of production, and it has invaluable significance for the diets and livelihoods of millions of people worldwide. Food and agriculture organization (FAO) has declared potato as a wholesome food. International Food Policy Research Institute (IFPRI) reported that major food source in the world (wheat, rice, corn, and potatoes) will steadily decrease up to 2050. Climate change has effected potato production globally. Future potato yields are likely to be affected by anthropogenic climate change as well as direct effects of emissions such as carbon dioxide (CO2) fertilization. Hence, it becomes imperative to study climate change impacts on potato with adaptive strategies and intervention to curtail impact for next generations as well as to feed a burgeoning world population.